(untitled) (Biological Sciences - PJSIR, 2010)
Using two threshold solid state nuclear detectors, mica and CN-85, the reaction of (14.0 MeV/u) Pb + Pb was studied. Reaction cross-section was determined experimentally as well as theoretically. Both elastic and inelastic data were used to calculate the experimental reaction cross-section. Theoretical reaction cross-section for 14.0 MeV/u Pb +Pb is 3809 ± 428 mb. Reaction cross-sections from elastic data were 3830 ± 500 mb and 3875 ± 500 mb for mica and CN-85, respectively, While reaction cross-sections calculated from inelastic data for mica and CN-85 were 4081 ± 500 mb and 4092 ± 500 mb, respectively. The partial reaction cross-sections for mica and CN-85 detectors were also determined. It was observed that partial cross- section of inelastic binary events in mica was higher than that in CN-85, whereas, cross section of 4 and 5-pronged events in mica were lower than those in CN-85. However, the number of three pronged events was identical in the two detectors. Using the difference in mass registration threshold of the two detectors, for fragment masses between 4 amu (registration thresholdof CN-85) and 30 u (registration threshold of mica) were searched, which were registered in CN-85 but not in mica.